Behavioral Pharmacology - From Basic to Clinical Research 2020
DOI: 10.5772/intechopen.90919
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacology of Secondary Metabolites from Plants with Anxiolytic and Antidepressant Properties

Abstract: Depression and anxiety currently rank as the second and fifth most common causes worldwide of years lived with disability-a reality that has intensified the search for new treatments. There are many studies of herbal extracts and secondary metabolites from plants used in traditional medicine due to their antidepressant and anxiolytic properties. Clinical and preclinical studies about some of the mechanisms of action of metabolites like alkaloids, terpenes, flavonoids, and sterols, among others, have documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 92 publications
(108 reference statements)
1
7
0
Order By: Relevance
“…Hesperidin is another flavonoid, which may raise hippocampal BDNF levels at 0.3 and 1 mg kg −1 daily dose for 21 days. Hesperidin produced antidepressant effect at 0.3 and 1 mg kg −1 on TST was found similar to the effects produced by imipramine at 15 mg/kg and fluoxetine at 32 mg kg −1 ( García-Ríos et al, 2020 ).…”
Section: Mechanisms Underlying the Anti-depressant Effects Of Phytoch...supporting
confidence: 58%
See 1 more Smart Citation
“…Hesperidin is another flavonoid, which may raise hippocampal BDNF levels at 0.3 and 1 mg kg −1 daily dose for 21 days. Hesperidin produced antidepressant effect at 0.3 and 1 mg kg −1 on TST was found similar to the effects produced by imipramine at 15 mg/kg and fluoxetine at 32 mg kg −1 ( García-Ríos et al, 2020 ).…”
Section: Mechanisms Underlying the Anti-depressant Effects Of Phytoch...supporting
confidence: 58%
“…In mice brains, fucosterol prevented the reduction in the levels of NA, 5-HT and 5-HTIIA caused by stress of FST, suggesting that the antidepressant effects are due to increased monoamines and decreased metabolism rate of 5-HT. Administration of β-sitosterol (30 mg kg −1 ) produced antidepressant effects in male mice on FST and TST similar to that of fluoxetine at a dose of 20 mg kg −1 ( García-Ríos et al, 2020 ). Another study reported the antidepressants potential of α- and β-amyrin (αβAMY) isolated from the stem resin of Protium heptaphyllum on FST.…”
Section: Mechanisms Underlying the Anti-depressant Effects Of Phytoch...mentioning
confidence: 99%
“…Thus, the phytochemical study is a topic of interest for the researcher to eValuate a lead compound to treat depression. Several phytochemicals (alkaloids, flavonoids, sterol, terpenes) are reported to have antidepressant effects [9]. Additionally, a few medicinal plants such as M. angolensis [32], N. sativa [33] R. rosea [34] are reported to have bilateral anxiolytic and antidepressant effects.…”
Section: Antidepressant Activitymentioning
confidence: 99%
“…Thus, it is imperative that new antidepressant drugs demonstrate improvement of these drawbacks. Several phytochemicals (alkaloids, flavonoids, sterol, terpenes) were reported to have an antidepressant effect [9]. Oximes (R 1 R 2 C = NOH) are chemicals containing nitrogen produced by organisms in all kingdoms of life [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many plants have anxiolytic and/or antidepressant potential and contain diverse phytoconstituents which may be exploited for the development of new drugs to treat these disorders, particularly in cases where patients do not respond to current medications. 17 , 18 The present study was undertaken to investigate the anxiolytic and antidepressant activity of the methanol extract of C. resiniferum (MECR) leaves using behavioral models in mice. As reactive oxygen species play an important role in the pathophysiology of depression and anxiety, 19 , 20 we sought to further determine the levels of total phenolics and flavonoids in MECR and investigate the antioxidant/free-radical scavenging potential of this extract.…”
Section: Introductionmentioning
confidence: 99%